2018
DOI: 10.1039/c7ra13272g
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the binding interaction of astilbin with bovine serum albumin: a spectroscopic study in combination with molecular docking technology

Abstract: The interaction of astilbin with bovine serum albumin was confirmed by multi-spectroscopic techniques and molecular docking methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 35 publications
5
40
0
Order By: Relevance
“…Blind docking experiment with the metal complex suggested (Figure A) that the Zn‐complex is attached on the outer surface of BSA molecule and the main driving forces of the attachment include coordination and hydrogen bonding with polar amino acid residues (Figure B). This is in accordance with the temperature dependent fluorescence and ITC data, in which the binding between BSA and the metal–ligand complexes were found to be exothermic . The standard free energy for the binding between BSA and complex 1 was found to be almost similar as obtained by molecular docking study.…”
Section: Resultssupporting
confidence: 89%
“…Blind docking experiment with the metal complex suggested (Figure A) that the Zn‐complex is attached on the outer surface of BSA molecule and the main driving forces of the attachment include coordination and hydrogen bonding with polar amino acid residues (Figure B). This is in accordance with the temperature dependent fluorescence and ITC data, in which the binding between BSA and the metal–ligand complexes were found to be exothermic . The standard free energy for the binding between BSA and complex 1 was found to be almost similar as obtained by molecular docking study.…”
Section: Resultssupporting
confidence: 89%
“…The K sv values were decreased as the temperatures increased (Table 1), indicating the primary involvement of static quenching process. Moreover, the biomolecular quenching rate constants (k q ) were found at a level of 10 12 M −1 s −1 , which were 100 times higher than the maximum scattering collisional quenching constant of various quenchers (2 × 10 10 M −1 s −1 ) [25]. Hence, the findings suggested that cloxyquin interacts with BSA via static process by the ground-state complex formation.…”
Section: Cloxyquin-induced Fluorescence Quenching Of Bsamentioning
confidence: 83%
“…BSA (4 µM) was titrated with various concentrations of cloxyquin (0, 1,5,10,15,20,25,30,40,60,70, and 80 µM) at different temperatures including 290, 300, and 310 K. The reactions were carried out in duplicate and its fluorescence spectra were detected in a range of 285-450 nm upon the excitation wavelength of 280 nm by using a QuantaMaster™ 40 spectrofluorometer (Photon Technology International, Inc., London, ON, Canada). The bandwidths of both excitation and emission units were set to be 1 nm.…”
Section: Steady-state Fluorescence Measurementmentioning
confidence: 99%
“…In order to confirm which mechanism has an important role in the interaction and to distinguish the ability of complexes to quench the emission of BSA, fluorescence quenching data were studied by the Stern–Volmer equation [Equation ]. F0/F=1+Ksv=1+τ0kq where F 0 and F are the fluorescence intensities in the absence and presence of quencher, respectively, K sv is the dynamic Stern–Volmer quenching constant [ m −1 ], k q is the quenching rate constant [ m −1 s −1 ], τ 0 is the average lifetime of BSA in the absence of any quencher and is generally equal to 2 × 10 −8 [s], and [Q] is the concentration of quencher [M]. Based on the linear fit plot of F 0 / F vs. [Q], the K sv values and then k q can be obtained.…”
Section: Resultsmentioning
confidence: 99%